Changes of atmospheric metal(loid) deposition from 2017 to 2021 at Mount Emei under China's air pollution control strategy. (1st June 2023) - Fu, Yuhan; Tang, Ya; Shu, Xi; Hopke, Philip K.; He, Lei; Ying, Qi; Xia, Zhonglin; Lei, Mengjie; Qiao, Xue
Abstract: Acid deposition and particulate matter (PM) pollution have declined considerably in China. Although metal(loid) and acid deposition and PM have many common sources, the changes of metal(loid) deposition in China in the recent decade have not been well explored by using long-term monitoring. Therefore, we analyzed the dry and wet deposition of eleven metal(loid)s (including Al, As, Ba, Cd, Cu, Cr, Fe, Mn, Pb, Sr, and Zn) from 2017 to 2021 at Mount Emei, which is adjacent to the most economic-developed region in western China (Sichuan Basin (SCB)). Anthropogenic emissions contributed to over 80% of the annual wet deposition fluxes of metal(loid)s and acids (SO4 2−, NO3 −, and NH4 + ) at Mount Emei, and the major source regions were the SCB, the Yunnan-Guizhou Plateau, and Gansu Province. Metal(loid) and acid deposition had similar seasonal variations with higher wet deposition fluxes in summer but higher wet deposition concentrations and dry fluxes in winter. The seasonal variations were partially associated with higher precipitation but lower pH in summer (968 mm and 5.52, respectively) than in winter (47 mm and 4.73, respectively). From 2017 to 2021, metal(loid) deposition did not decline as substantially as acid deposition (5.6%–30.4%). Both the annual total deposition fluxes and concentrations of Cr, Cu, Sr, Ba, and Pb were even higher in 2020–2021 than in 2017–2018. The inter-annual and seasonal changes implied the responses of metal(loid) deposition to anthropogenic emission changes were buffered (e.g., transformation, dilution, and degradation) by precipitation rates, acidity, natural emissions, and chemical reactions in the atmosphere, among others. Graphical abstract: Image 1 Highlights: Metal(loid) deposition did not decline as substantially as acid deposition. Seasonal variations of metal(loid)s were affected by precipitation rates and pH. The major source regions were Sichuan Basin, Yunnan-Guizhou Plateau, and Gansu. Anthropogenic emissions greatly contributed to acid and metal(loid) deposition. Ecological risk was low but the ecosystem responses still need to be observed.